Systematic study of political ecology and the role of local community in the development of the Ibu Kota Nusantara - Salsa Muafiroh; Rudy Parluhutan Tambunan (Sustainable Urban Development and Environmental Impact Journal, 2025)
Background: The development of the Indonesian Capital City (IKN) represents a transformative initiative aimed at relocating the capital from Jakarta to East Kalimantan to mitigate environmental degradation and promote equitable regional growth. This study investigates the ecological and social implications of IKN development by reviewing relevant literature and emphasizing the role of local communities and pentahelix collaboration in fostering sustainable outcomes. Methods: A systematic literature review was conducted using PRISMA and SALSA methodologies to screen 215 articles, of which 15 met the inclusion criteria for detailed analysis. Findings: The review revealed significant challenges—including ecological disruption, social inequality, and the marginalization of indigenous rights—while identifying pentahelix collaboration as a critical mechanism for integrating efforts from government, academia, the private sector, media, and community stakeholders. Conclusion: The study concludes that enhancing pentahelix collaboration and empowering local communities are essential for mitigating adverse impacts and achieving sustainable, inclusive development in the IKN context. Novelty/Originality of this article: This research introduces a novel framework that links political ecology with social justice and ecological sustainability, offering innovative insights for policy interventions that prioritize long-term equity and environmental stewardship.